Logiki drzew derywacyjnych - Krysztofiak, Wojciech (Filozofia Nauki, 2007)
The paper presents the construction of a new class of logics, which are called logics of derivational trees. The presentation comprises three sections: (i) intuitive psychological motivations for these logics stemming from some results of developmental psycho-linguistics (Piaget, Chomsky), (ii) the construction of formal calculus with help of algorithmic tools, and (iii) the construction of set-theoretic semantic model for our logic. They determine criteria of valid deriving and transforming structures which are usually described in the literature as derivational trees. These structures are used in linguistics or in computational sciences as tools of modelling deep sentential structures or information-bases. Furthermore cognitive anthropologists notice that most of our ordinary taxonomies arranging the experienced world in our Lebenswelt possess various tree-structures. It seems that our abilities of applying tree-structures (without explicit knowledge concerned with algebraic mechanisms of construing tree-structures) in various segments of our life are mental and behavioral manifestation of some special logical disposal belonging to the machinery of logical competence in general. It is interesting to put the hypothesis according to which the competence of construing and applying tree-structures is even more primitive than the competence of applying logical rules of natural deduction. The presented calculus possesses some peculiar feature, namely its formal language is composed of expressions of three syntactic levels. In standard, formal languages all expressions may be divided as belonging to two levels: the level of formulas and the level of constituents of formulas. In the language of derivational trees there are distinguished the following levels: (i) the level of lexical expressions, (ii) the level of derivation-expressions, (iii) and finally the level of transformation-expressions. These last category fulfils the role of formulas. Proofs are appropriate sequences of derivation-expressions. However what is proved is not a derivation-expression but it is a transformation-expression. The peculiarity of our logic consists in that an expression which is proved, does not belong to the category of constituents of proofs.